Obstacles to accompanying first-year university students from the point of view of accompanying professors and students under guardianship “An exploratory study into the results of cases that applied educational accompaniment.” - khadidja DAAMACHE (Social Sciences Journal, 2021)
The present study aims at detecting the obstacles of pedagogical accompaniment for the first-year university students and to achieve the objective of the study. In the same academic year 2017/2018, the results of the study revealed that the most important obstacles of pedagogical accompaniment from the point of view of the accompanying professors are: lack of communication skills between faculty members and students; The teaching staff from halls to practice them properly should not understand the necessity of applying pedagogical accompaniment. As for the university student: Lack of awareness of university students of the importance of pedagogical accompaniment in terms of alleviating the problems faced, in overcoming the difficulties in the completion of graduation notes, in choosing the future profession, in adapting them to the regulations and laws of the university, in identifying the outlets of university training.